Analysis and application evaluation of precoding method based on low-band communication system - Di WU; Yijun SUN; Zherui MA; Tao MA (Dianxin kexue)
In the communication system, limited by the influence of channel correlation, in general, the lower the operating frequency band of the antenna system, the larger the spacing of the antenna elements, and the larger spacing of the array elements was not conducive to the reduction of the physical size of the communication device. An antenna system with an array spacing was analyzed, which could achieve a smaller physical size than an antenna system with a conventional array spacing. Three kinds of transmit antenna systems were selected for performance comparison: 8-antenna λ /2 system, 4-antenna λ /2 system (of comparable size), and 8-antenna λ /2 system (with the same number of elements). Also their beamforming effect, interference suppression capability and channel capacity were analyzed. Simulation results show that the antenna system can achieve relatively good performance.